2011
DOI: 10.1128/jcm.01217-11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Six Commercial Nucleic Acid Amplification Tests for Detection of Neisseria gonorrhoeae and Other Neisseria Species

Abstract: Molecular detection ofNeisseria gonorrhoeae causes the second most prevalent bacterial sexually transmitted infection (STI) in men and women globally (42). As clinical signs of gonococcal infection may overlap with those of other STIs, laboratory testing is crucial for appropriate diagnosis and subsequent adequate treatment. The accurate diagnosis of gonorrhea relies on laboratory tests that are sensitive, specific, reproducible, and robust because of nonspecific clinical manifestations or lack of symptoms in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
83
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(86 citation statements)
references
References 39 publications
0
83
0
3
Order By: Relevance
“…Several commercially available real-time PCR assays enable this double detection (3). Trichomonas vaginalis is the most prevalent nonviral sexually transmitted disease pathogen in the world, but it remains poorly diagnosed, as are Mollicutes (Ureaplasmas and Mycoplasmas), which are difficult to cultivate (4)(5)(6).…”
mentioning
confidence: 99%
“…Several commercially available real-time PCR assays enable this double detection (3). Trichomonas vaginalis is the most prevalent nonviral sexually transmitted disease pathogen in the world, but it remains poorly diagnosed, as are Mollicutes (Ureaplasmas and Mycoplasmas), which are difficult to cultivate (4)(5)(6).…”
mentioning
confidence: 99%
“…e must strenuously disagree with Tabrizi et al that "Supplementary testing for confirmation of N. gonorrhoeae NAATs remains recommended with all samples tested, in particular those from extragenital sites" (emphasis ours) (6). This may reflect Australian guidelines, but the generalization is unfortunate.…”
mentioning
confidence: 59%
“…Performance data to date show excellent sensitivity and specificity for urogenital specimens (3-7), and it has been suggested that the assay does not require a second test to confirm urogenital positive results (6). Also, to our knowledge, there have been no definitive reports of the assay cross-reacting with commensal Neisseria strains (3,8); while initial testing in a study by Tabrizi et al (8) showed that the cobas 4800 NG assay cross-reacted with two commensal Neisseria strains, both were negative upon retesting using fresh cultures (8). Herein, we report the first clinical demonstration of a Roche cobas 4800 NG falsepositive result obtained from a pharyngeal swab sample and caused by a reproducible cross-reaction with a commensal Neisseria strain.…”
mentioning
confidence: 91%